تأثير نقص العناصر النادرة في بعض الصفات المورفولوجية (الشكلية) والإنتاجية للقطن باستخدام المزارع الرملية - عبد العزيز محمد; بوعيسى عبد العزيز; مياسة غيداء (Latakia University Journal -Biological Sciences Series, 2019)
نفذ البحث بهدف دراسة تأثير نقص العناصر النادرة في بعض مكونات محصول القطن، بزراعة بذور الصنف حلب 33 ـ 1 في أصص بلاستيكية معبأة بالرمل. استخدمت، معاملات سمادية هي: معاملة محلول هوجلند شاهد (T1) ومعاملة هوجلند (T2) ومعاملة هوجلند عدا البورون (T3) ومعاملة التسميد العضوي (T4) ومعاملة التسميد المعدني (T5) ومعاملة التسميد العضوي والمعدني معاً (T6) بينت الدراسة النتائج الآتية: تفوقت معاملة الشاهد (محلول هوجلند) في طول النبات وعدد الفروع الثمرية، عدد البراعم الزهرية، وعدد الجوزات/النبات ووزن الجوزة/غ والمحصول البيولوجي والإنتاجية في حين انخفضت نسبة التساقط. بالمقارنة مع المعاملات المدروسة (T6, T5, T4, T3, T2). انخفضت معنوياً متوسطات الصفات المدروسة إلى أقل قيم لها عند معاملة التسميد المعدني (T5) ومعاملة التسميد العضوي (T4) ومعاملة التسميد العضوي والمعدني معاً (T6) لعدم قدرتها على تأمين متطلبات النبات من العناصر النادرة وكان الانخفاض معنوياً عند المعاملة (T3) مقارنة بالمعاملة (T1) و(T2) لكنها أفضل من المعاملات الأخرى. The research was carried out to study the effect of trace elements deficiency on some yield components of cotton crop (Variety Aleppo 33 - 1) planted in pots containing sandy soil. Six fertilizer treatments were used: Hogland (T1) as a control, 1/2 Hogland (T2), Hogland without boron (T3), organic fertilizer (T4), mineral fertilizer (T5), organic and mineral fertilizer together (T6). The results showed the following: control treatment (Hogland T1) significantly increased the plant height, number of fruit branches, number of fruit buds, number of bolls per plant, boll weight per gram, biological crop, and productivity. The percentage of falling was decreased in comparison with other treatments (T2, T3, T4, T5, T6). The average of studied characters was significantly decreased to the lower values in mineral fertilization (T5), organic fertilization (T4), and both organic and mineral fertilization (T6) because of some trace elements deficiency. The decrease was significant in treatment (T3) in comparison with (T1) and (T2) treatments, but it was better than other treatments.